RATIONALITY OF SUBMISSION OF PROPOSED IMPLEMENTATION OF SHARIA FINANCIAL INSTITUTIONS IN ACEH - T. Muhammad Armya (Jurnal Ilmiah Mahasiswa Fakultas Ilmu Sosial & Ilmu Politik, 2022)
Based on the Law on the Government of Aceh, it is explained that the Aceh government has the authority to regulate and manage government affairs in all public sectors except for government affairs which are under the authority of the Government, the authority in question gives birth to the Qanun on the Principles of Islamic Shari'a, the essence of the regulation is to oblige the government and the people of Aceh to apply Islamic Shari'a kafaah. One aspect that is described in the Qanun on the Principles of Islamic Shari'a is related to Shari'a Muamalah or Sharia finance. therefore causing the government to have demands and duties to draft and ratify the Qanun on Sharia Financial Institutions (LKS). However, in the stage of drafting an academic paper, it is considered to have a problem of consideration in terms of the legal basis, causing some parties to feel disadvantaged from the formation of the LKS Qanun. This study is to explain the rationality of the Submission of Proposals for the Implementation of Islamic Financial Institutions in Aceh. The research approach uses a qualitative approach. Primary data collection techniques through direct interviews with informants, while secondary data through documentation/library. The results of this study indicate that the proposed implementation of the LKS Qanun is included in instrumental rationality and value-oriented rationality. Instrumental rationality in the LKS Qanun, can be seen from the goals to be achieved from the Aceh government, which is a form of the aspirations of the Acehnese people, which is directly mandated in the Qanun on the Principles of Islamic Sharia to regulate the financial system in Aceh based on Islamic Sharia principles. . Meanwhile, in terms of the rationality of the values contained in the proposal for the implementation of the Qanun LKS, it can be seen clearly in the rationale of how a Qanun LKS was built, whose main purpose is to perfect the worship of the Acehnese people by avoiding all forms of usury practices (believing values) that exist in the conventional financial system. Keywords: Rationality, LKS